Metabolic Consequences of Supplemented Methionine in a Clinical Context. (1st October 2020) - Ligthart-Melis, Gerdien C; Engelen, Mariëlle P K J; Simbo, Sunday Y; Ten Have, Gabrie A M; Thaden, John J; Cynober, Luc; Deutz, Nicolaas E P
ABSTRACT: The central position of methionine (Met) in protein metabolism indicates the importance of this essential amino acid for growth and maintenance of lean body mass. Therefore, Met might be a tempting candidate for supplementation. However, because Met is also the precursor of homocysteine (Hcy), a deficient intake of B vitamins or excessive intake of Met may result in hyperhomocysteinemia (HHcy), which is a risk factor for cardiovascular disease. This review discusses the evidence generated in preclinical and clinical studies on the importance and potentially harmful effects of Met supplementation and elaborates on potential clinical applications of supplemental Met with reference to clinical studies performed over the past 20 y. Recently acquired knowledge about the NOAEL (no observed adverse effect level) of 46.3 mg · kg -1 · d -1 and the LOAEL (lowest observed adverse effect level) of 91 mg · kg -1 · d -1 of supplemented Met will guide the design of future studies to further establish the role of Met as a potential (safe) candidate for nutritional supplementation in clinical applications.